Association between severity and locations of primary hyperhidrosis and quality of life among medical students - Catherine Patricia Soetedjo; Lorettha Wijaya; Regina Regina; Yunisa Astiarani (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: Primary hyperhidrosis is a condition of excessive sweating on certain parts of the body with unknown cause. The severity and location of primary hyperhidrosis vary and are thought to affect the quality of life.Purpose: The study aims to determine the association between severity and locations of primary hyperhidrosis and quality of life in medical students.Methods: This study was conducted on 77 medical students at Atma Jaya Catholic University of Indonesia. Hyperhidrosis Disease Severity Scale (HDSS) questionnaire and Hyperhidrosis Quality of Life Index (HidroQoL) questionnaire were used. Data analysis was performed using Chi-Square.Results: The prevalence of primary hyperhidrosis was 15.33%. Mild-moderate hyperhidrosis was found in 77.9% respondents, while severe-very severe hyperhidrosis was found in 22.1% respondents. The location of hyperhidrosis was found in palmar (66.1%), axillary (28.6%), plantar (1.0%), and other locations such as the face, thigh, and back (9.1%). The score of the daily activity domain (29.65 ± 21.96) was higher than the psychosocial score (27.92 ± 20.46). Data showed that 33.3% of respondents with mild-moderate hyperhidrosis and 82.4% of respondents with severe-very severe hyperhidrosis’ quality of life were affected by their excessive sweating (p=0,000). As many as 34.0% of respondents with palmar hyperhidrosis and 54.5% with axillary hyperhidrosis’ quality of life were all affected by their conditions (p=0,106).Conclusion: We found a significant association between the severity of primary hyperhidrosis and the quality of life, and no significant association between the location of primary hyperhidrosis and quality of life among medical students.